Polymers with Alkylsulfanyl Side Chains for Bulk Heterojunction Solar Cells: Toward a Greener Strategy. Issue 16 (5th June 2017) - Tassinari, Francesco; Libertini, Emanuela; Parenti, Francesca; Ballarin, Barbara; Nicola, Francesco Paolo Di; Lanzi, Massimiliano; Mucci, Adele
Abstract : Materials for organic solar cells can be synthesized without the use of organotin intermediates nor palladium catalysts. The synthesis and properties of three copolymers obtained through a Knoevenagel polycondensation reaction are reported. The alkylsulfanyl side chains on the thienyl rings improve the performances of the device with respect to alkyl chains. Abstract : The synthesis and properties of three copolymers obtained through a Knoevenagel polycondensation are reported. They are soluble in organic solvents, filmable, and solvatochromic. They are characterized through gel permeation chromatography, NMR and UV–vis spectroscopies, cyclic voltammetry, and atomic force microscopy. They display some proneness to form π‐stacks, broad absorptions up to about 700 nm, highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) energies that fit those of [6, 6]‐phenyl‐C61‐butyric acid methyl ester ([60]PCBM). The polymers are incorporated in blends with PCBM within bulk heterojunction devices. The best results are found for polymer solar cells obtained fromP1 (2.7% power conversion efficiency). The insertion of alkylsulfanyl chains improves the photovoltaic performances, with respect to those of alkyl‐substituted analogous polymers. The J sc of the devices are greatly enhanced, supporting the employment of (alkylsulfanyl)thienyl units as base units in photoactive materials.